Potential of using natural and synthetic binder in wood composites - Liew, Kang Chiang; Tan, Yufeng; Charles Michael Albert; Vinodini Raman; Michelle Boyou (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The physical and mechanical properties of particleboard bonded with different cooking percentages of seaweed (Kappaphycus alvarezii), with different percentages of starch and different percentages of adhesives, and wood plastic composite (WPC) from High-Density Polyethlene (HDPE) with Acacia mangium wood powder were determined in this study. Seaweed mixed with different percentages of sulfuric acid (30%, 50%, 70%) and Sodium Hydroxide (70%, 50%, 30%) were prepared as a binder for particleboard. For a starch-based binder, different percentages of starch (10%, 15%, 20%) were prepared, before producing particleboard with different amounts of binder (20%, 25%, 30%). As for WPC, wood powders were bonded with different percentages of HDPE content (70%, 80%, 90%). Results indicated that WPC at 90% HDPE shows the best performance in the water absorption (0.07%) and thickness swelling test (2.54%). Starch-based particleboard recorded the highest Modulus of Elasticity (MOE) value (1115.07 N/mm2 at 15% starch with 30% amount of binder), while WPC (90% HDPE) and starch-based particleboard (10% starch with 20% amount of binder) both recorded the highest Modulus of Rupture (MOR) at the same value, which is 7.84 N/mm2. Starch-based particleboard has a better internal bond, which is 0.05 N/mm2. However, seaweed-based particleboard has a higher density value, which is 0.6 g/cm3.